Managing without management : a post-management manifesto for business simplicity - Koch, Richard, 1950- (Nicholas Brealey, 1996)
Has management outlived its usefulness? Six forces threatening management. The revolution that has not happened. Managing without management. Customer power. Information power. Investor power. Global market power...